2014
DOI: 10.1007/s11325-013-0920-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of musculoskeletal pain on sleep architecture in patients with obstructive sleep apnea

Abstract: Patients with obstructive sleep apnea and chronic musculoskeletal pain sleep not only significantly less but also with inferior sleep quality. Their REM sleep is also less in duration and its onset is delayed. Despite low TST and SE, these patients may not exhibit sleepiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
1
18
2
Order By: Relevance
“…Among the factors affecting pain sensitivity are quantity and quality of sleep, which are both important in maintaining homeostasis of pain-regulatory processes 21 ) . Sleep disturbances are a common problem in patients with chronic pain 23 ) , and evidence suggests that sleep loss causes hyperalgesia 24 ) . Data from patients with OSAS supports a correlation between sleepiness and pain sensitivity 25 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the factors affecting pain sensitivity are quantity and quality of sleep, which are both important in maintaining homeostasis of pain-regulatory processes 21 ) . Sleep disturbances are a common problem in patients with chronic pain 23 ) , and evidence suggests that sleep loss causes hyperalgesia 24 ) . Data from patients with OSAS supports a correlation between sleepiness and pain sensitivity 25 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies investigating the relationship between sleep and pain have focused on sleep disturbances in pain patients, and few studies have investigated chronic pain in OSAS patients. A recent retrospective study showed that 200 of 393 patients with OSAS had chronic musculoskeletal pain 23 ) . In this study, no significant differences were observed in age, BMI, or gender between the OSAS and OSAS-plus-pain groups; however, 96.7% of subjects in the study were male.…”
Section: Discussionmentioning
confidence: 99%
“… 99 Chronic pain patients with sleep apnea show reduced sleep duration and poorer sleep quality than those with sleep apnea without pain. 100 A large prospective study investigating the relationship between OSA and temporomandibular disorder 101 showed that people with a history of OSA are more likely to develop chronic pain. A recent animal study suggests that sleep deprivation differentially impacts obese vs lean animals on pain sensitivity; when sleep was fragmented, pain threshold was increased in the lean but not in obese mice at one of the testing times during a day.…”
Section: Potential Mechanisms Underlying the Obesity–pain Linkmentioning
confidence: 99%
“…Type 2 diabetes is frequently associated with OSA, with obesity as a common risk factor [ 32 ]. In persons with OSA and chronic musculoskeletal pain, Nadeem et al [ 89 ] found that the pain significantly shortened sleep time and lessened the quality of sleep. Asghari et al [ 48 ] found no association between OSA and the severity of depression and anxiety symptoms; however, Rezaeitalab et al [ 45 ] found that 53.9% of the study population experienced anxiety and 46.1% depression, and that OSA severity was associated with the frequency of anxiety.…”
Section: Discussionmentioning
confidence: 99%